Effects of vaginal progesterone and placebo on preterm birth and antenatal outcomes in women with singleton pregnancies and short cervix on ultrasound: a meta-analysis - Peng, Limin; Gao, Yan; Yuan, Chengkun; Kuang, Hongying (Frontiers in Medicine, 2024)
Background: vaginal progesterone in preterm birth and adverse outcomes caused by cervical insufficiency remains controversial. To address it, the effect of vaginal progesterone on preterm delivery and perinatal outcome of single pregnancy women with short cervix (less than 25 mm) was systematically evaluated by meta-analysis. Methods: "vaginal progesterone", "placebo", "ultrasound", "cervix", "singleton pregnancy", "preterm birth", and "antenatal outcomes" were entered to screen clinical studies PubMed, Embase, and the Chinese Biomedical Literature Database (CBM). The study population consisted of women with singleton pregnancies and a short cervix on ultrasound, and were assigned into the progesterone group (n=1,368) and the placebo group (n=1,373). Treatment began after the patient was diagnosed with short cervix until delivery. Neonatal survival rate, Neonatal Intensive Care Unit (NICU) admission rate, respiratory distress syndrome (RDS), intraventricular hemorrhage (IVH), neonatal mortality, and birth weight < 1,500 g were analyzed. Results: 8 articles, totaling 2,741 study subjects, were enrolled. The progesterone group exhibited an obvious reduced rate of preterm birth at < 34 weeks (OR = 0.67, 95% CI: 0.53~0.84; Z=3.53, P=0.004), preterm birth at < 32 weeks (OR = 0.46, 95% CI: 0.28~0.77; Z=2.99, P=0.003), NICU admission rate (OR = 0.45, 95% CI: 0.30~0.66; Z=0.15, P<0.0001), RDS rate (OR = 0.42, 95% CI: 0.28~0.63; Z=4.25, P<0.0001), IVH incidence rate (OR = 0.40, 95% CI: 0.17~0.95; Z=2.08, P=0.04), neonatal mortality (OR = 0.25, 95% CI: 0.13~0.46; Z=4.39, P<0.0001), and proportion of neonates with birth weight < 1,500 g (OR = 0.45, 95% CI: 0.32~0.64; Z=4.50, P<0.0001).vaginal progesterone lowered the incidences of preterm birth and adverse pregnancy outcomes in women with singleton pregnancies and a short cervix.